BEHAVIORAL MODELS AND THEORIES APPLIED TO STUDIES ON THE ADOPTION OF BANKING TECHNOLOGIES (CIPEEX, 2025)
Various elements can influence the intention to use technology, reflecting a wide range of individual variables. Despite this, behavioral models and theories remain valuable, serving as a basis for research that seeks to understand consumer needs and improve service offerings. This debate on these aspects is not recent and is considered relevant due to the difficulties some people have in accessing new banking technologies, whether due to a lack of knowledge, skills or a conservative profile averse to change, which ends up resulting in the failure of new systems and a preference for conventional means. The aim of the research was to analyze the models, behavioral theories and influencing factors found in studies on the adoption of banking technologies. The study is an integrative review of a qualitative nature, whose guiding question addressed the factors associated with the adoption of banking technologies by consumers. The searches were carried out in the CAPES Periodicals and Spell Electronic Library databases, using descriptors in English and Portuguese to maximize the results: Acceptance, Technology, User, Banking, Customer, Mobile Banking and Technology. The inclusion criteria considered only studies from the last five years, available in English, Portuguese and Spanish, which contained “Technology” or “Acceptance” in the title. Off-topic, unavailable in full and duplicate studies were excluded. After analyzing the results, those with different methods and objectives were approved, but which still showed results related to behaviors and influencing factors in the adoption of financial institutions and technology. In the end, eight articles were considered relevant. The results of the research showed that two articles were reviews, while the others consisted of original investigations with data collection using questionnaires directed at the target audience. Each study presented different theories or models, formulating and testing their own hypotheses. The topics covered also included the intention to continue using banking technologies, social influence, cultural and demographic issues. Among the main models and theories used in the seven selected studies were the EDM, TCB, ECT, Three-Dimensional Model, TAM and UTAUT. Of these, TAM and UTAUT were the most frequently applied. Only one study did not use a specific model, focusing only on answering the question about the low adoption of banking technologies in Jaipur. There is a diversity of conclusions, since the studies were carried out in different regions and countries, with three of them conducted in Brazilian settings while the other three covered foreign countries located on the Asian continent, including Malaysia, Saudi Arabia and India, more specifically in the city of Jaipur. The two reviews presented the results of research carried out in various countries. Thus, it was found that factors such as the location and culture where the research is conducted, the demographic and social profile of consumers, as well as familiarity with new technologies, play a significant role in the user's perspective on the adoption rate of fintechs and the use of digital payments.
Keywords: adoption; banking; behavioral; techonology